APPLICATION OF GRAVITATIONAL PROSPECTING IN INTEGRATED COMPLEX GEOPHYSICAL METHODS FOR STUDYING SALT-DOME STRUCTURES OF DNIEPER-DONETS DEPRESSION - Omelchenko, V.; Pigulevskiy, P.; Dubrov, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper discusses feasibility of gravity survey and ways to improve its geological effectiveness in integrated complex of geophysical investigations for studying salt-dome structures. Study of morphology of salt diapirs and buried salt structures, prediction of oil and gas potential in structural traps related to them are problems of great importance. Physical basis of application of gravitational, magnetical, electrical prospecting for studying salt-dome structures are explained. Different forms of salt structures exposured in gravitational field are described by the examples of certatin cases (mainly negative isometric anomalies of high and hightened intensity). Authors also marked a significant trend of structures to form groups, which are extended in north-west direction typical for Dnieper-Donets Depression (DDD), and also form lengthy lineaments of sub-meridional and north-east orientation, which are explained as their relation to ancient faults in Precambrian basement. Main geological results obtained for morphology large Chutovsko-Rospashnovsko-Belouchovsky and Andreevsky salt diapirs, located in the central part of Dniepr graben, are based on volumetric density modeling. Authors would like to note that if gravitational method be used during the exploration process, it might be possible to avoid erroneous prospecting boreholes that have gone out of stock sal. The ways for improvement of gravimetrical exploration at studyin salt tectogenesis are suggested. Among the main ways are application of effective technological programs for volumetric density modeling, detailed studying of density profiles, realization of high-precision large scale survey mapping (1:10 000) and integration with other geophysical methods for coherent models construction.
Keywords: gravimetric survey; Dnieper-Donets Depression; salt-dome structures